Andreas Rio Adriyanto MEMAHAMI PERILAKU GENERASI Z SEBAGAI DASAR PENGEMBANGAN MATERI PEMBELAJARAN DARING - Andreas Rio Adriyanto; Imam Santosa; Achmad Syarief (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2020)
Virtualization in learning provides a barrier between students and lectures. The existence of a digital partitioncreating a boundary that gives freedom of students to collect data and information. Previous studies haveshown the low engagement on students in completing online learning courses. Although there are still weaknesses,the implementation of online learning is a necessity. Students who will use this online learning aregeneration Z. They were born in the period of 1997-2012 when computer technology and the internet haddeveloped. They are more familiar with the concept of digital information technology before getting to know theconcept of school. This generation is also referred to as digital natives. This research uses literature studiesand surveys on digital generation in relation to their digital activities. The results of this study are expected tobe one source of understanding the behavior of Generation Z as the basis of developing online learningmaterials.